Estrategias metodológicas en el área de lengua y literatura y su influencia en el proceso de enseñanza aprendizaje en los estudiantes del 6to EGB de la UE Adolfo María Astudillo cantón Babahoyo Provincia Los Ríos. 2022 - Utreras Hurtado, Karen Andrea (2022)
Methodological strategies are essential when teaching classes because with the application of strategies, students have the opportunity to have a better understanding of educational issues, with the proper use of methodological strategies, teachers and students achieve a correct teaching-learning process. In the teaching-learning process there are two fundamental actors, the teacher and the student, it is necessary that there is a good relationship between teaching and learning. In the area of Language and Literature, it is essential that teachers implement strategies to achieve dynamism in the class and ensure that students acquire knowledge. This research project was carried out in the EU Adolfo María Astudillo canton Babahoyo province of Los Ríos; it was possible to show that the teachers did not carry out a correct implementation of methodological strategies in the area of Language and Literature in the teaching-learning process in the students of the 6th EGB. The 74 EGB teachers were taken from the population and a sample of 20 teachers who were preceded by a virtual survey, the quantitative methodology was used, resulting in the implementation of methodological strategies in the area of Language and Literature are considered necessary. by teachers in the teaching-learning process and that some teachers are not making a correct implementation of strategies. Finally, a guide of methodological strategies in the area of Language and Literature is proposed to solve the problem of this research.